2020
DOI: 10.15503/jecs2020.2.171.182
|View full text |Cite
|
Sign up to set email alerts
|

A Systematic Review of the Approaches Enhancing the Mathematics Achievement

Abstract: Aim. The aim of this study is to analyse the conducted studies in order to reveal the effect of the strategies, methods and techniques used in elementary school mathematics courses, to apply critical strategies based on impartiality, and to critically evaluate and synthesize them. Methods. In this systematic review study, Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) Statement was used in order to prepare the systematic review protocol. The studies were based on students’ ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 6 publications
0
3
0
Order By: Relevance
“…Studies have confirmed cultural background as a provident tool for teaching and learning mathematics (Amoako Atta & Asiedu-Addo, 2021; Cai & Wang, 2010;Ltd, 2020;Smith-Maddox, 1998). It is instructive to note that countries that use their local language to teach mathematics usually perform better than those that use a second language to teach mathematics (Papers OECD Library;Mullis & Martin, 2017;Zou, 2019).…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…Studies have confirmed cultural background as a provident tool for teaching and learning mathematics (Amoako Atta & Asiedu-Addo, 2021; Cai & Wang, 2010;Ltd, 2020;Smith-Maddox, 1998). It is instructive to note that countries that use their local language to teach mathematics usually perform better than those that use a second language to teach mathematics (Papers OECD Library;Mullis & Martin, 2017;Zou, 2019).…”
Section: Introductionmentioning
confidence: 97%
“…However, as mathematics educators, there is a need for ongoing research-based professional learning that focuses on the sociopolitical turn of mathematics education and mathematical pedagogies that are equitable and culturally responsive (Alangui, 2017;Meaney et al, 2021b;Rosa et al, 2016). Studies continue to show that equitable practices combined with high expectations, high-quality content, and strong community relationships have a positive effect on mathematics learning and achievement (Ltd, 2020) Developing positive cultural and social identities requires grounding mathematics instruction in students' languages, cultures, and communities while equipping them with the mathematical skills necessary to flourish in the dominant society (Parker et al, 2017). Reading the mathematical word, academic performance, and influencing students' (and teachers') mathematics orientation is the mathematics educational goals of Gutstein (2006) cited in (Gutstein, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Mathematics educators need research-based professional development on the sociopolitical turn of mathematics education and fair, culturally responsive mathematical pedagogies. Studies continue to show that egalitarian rules, high standards, high-quality content, and strong community linkages increase mathematics learning and achievement (Ltd, 2020). Developing appropriate cultural and social identities demands grounding mathematics instruction in students' languages, cultures, and communities while offering them mathematical tools to succeed in the dominant society (Parker et al, 2017).…”
Section: Introductionmentioning
confidence: 99%